Permafrost creep within a recently deglaciated glacier forefield: Muragl, Swiss Alps - A. Kääb; C. Kneisel (Permafrost and Periglacial Processes)
Photogrammetric measurements of surface movement, 1981–94, on the Muragl glacier forefield (Swiss Alps) are compared to direct current resistivity surveys for the same area. At three locations isolated patches of frozen sediments were inferred, each about 10,000–20,000 m2 in area. These were deforming at surface velocities of up to 50 cm per year. The locations where creep was observed coincide well with areas where two‐dimensional (2D) resistivity surveys suggest ice is present within the ground. Copyright © 2005 John Wiley & Sons, Ltd.